Effective engagement and involvement with community stakeholders in the co-production of global health research. (15th February 2021) - Tembo, Doreen; Hickey, Gary; Montenegro, Cristian; Chandler, David; Nelson, Erica; Porter, Katie; Dikomitis, Lisa; Chambers, Mary; Chimbari, Moses; Mumba, Noni; Beresford, Peter; Ekiikina, Peter O; et al.
Abstract : Doreen Tembo and colleagues argue that small changes as well as larger system-wide changes can strengthen citizens' contribution to knowledge in health research